How Myths about Language Affect Education : What Every Teacher Should Know - Johnson, David, 1967- (Book collections on Project MUSE., 2008)
"How Myths about Language Affect Education: What Every Teacher Should Know clarifies some of the most common misconceptions about language, particularly those that affect teachers and the decisions they make when they teach English language learners. The chapters in this book address myths about language in general, about first and second language acquisition, about language and society, and about language and thinking. Each chapter concludes with activities for teachers thai give examples, exorcises, or simple questions that relate directly to teachers' everyday dealings with ELLs and language." "How Myths about Language Affect Education is not intended to be a complete introduction to linguistics; it does not contain information on phonetics or complex syntactic explanations, and technical jargon is kept to a minimum. The aim of this book is not to settle language issues but rather to highlight popular misconceptions and the ways that they influence debates regarding language and affect language policies in and out of the classroom."--Jacket